2006
DOI: 10.1007/s10509-005-9002-y
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Wave-Particle Interactions on Double-Hump Distributions of the H + Polar Wind

Abstract: A Monte Carlo simulation is used in order to study the effects of wave-particle interactions (WPI) on H + distributions in the polar wind outflow. The simulation also considers effects of the gravity, the polarization electric field, the divergence of geomagnetic field lines and H + −O + Coulomb collisions. The proton velocity distribution function (VDF) and the profiles of its moments (density, bulk velocity, parallel and perpendicular temperatures, heat flux. . .) are found for different levels of WPI, i.e.,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2007
2007
2014
2014

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 23 publications
0
4
0
Order By: Relevance
“…In subsequent Monte Carlo simulations, Barakat and Barghouthi (1994) examined the effect of wave-particle interactions on the velocity distribution of polar wind H + and O + ions flowing out of the ionosphere along magnetic field lines (Barakat et al 1995). Effects of wave-particle interactions on Lorentzian VDFs were analyzed in Pierrard and Barghouthi (2006). More recently, Barghouthi et al (2007) analyzed also the effect of finite electromagnetic turbulence wavelength on the highaltitude and high latitude O + and H + outflows.…”
Section: Monte Carlo Simulationsmentioning
confidence: 99%
“…In subsequent Monte Carlo simulations, Barakat and Barghouthi (1994) examined the effect of wave-particle interactions on the velocity distribution of polar wind H + and O + ions flowing out of the ionosphere along magnetic field lines (Barakat et al 1995). Effects of wave-particle interactions on Lorentzian VDFs were analyzed in Pierrard and Barghouthi (2006). More recently, Barghouthi et al (2007) analyzed also the effect of finite electromagnetic turbulence wavelength on the highaltitude and high latitude O + and H + outflows.…”
Section: Monte Carlo Simulationsmentioning
confidence: 99%
“…(6) and (7) is the weakest there. The effect of Coulomb collisions may change the shape of the ion velocity distribution (Pierrard and Barghouthi, 2006), which, in turn, affects the heat flux.…”
Section: Applicability Of Our Resultsmentioning
confidence: 99%
“…The results of the polar wind study indicated that both the density and outflow velocity of the O + ions are strongly related to the level of the wave energy; the escape flux of these heavy ions could be enhanced by a factor of 10 5 with strong WPI. Pierrard and Barghouthi (2006) have also studied the effects of the WPI on the double-hump H + ion velocity distribution function in the polar wind.…”
Section: Modeling Of Non-classical Polar Wind Effectsmentioning
confidence: 99%